EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DAN TEAM GAME TOURNAMENT (TGT) PADA PRESTASI BELAJAR DITINJAU DARI MOTIVASI SISWA - Erny Untari (Jurnal Muara Pendidikan, 2020)
The purposes of this study are to determine: (1) which one have a better achievement, students who taught by learning model NHT or Tgt type. (2)which one have a better achievement, students who have high, middle, or low achievement motivation. (3) is there any interaction between learning model and achievement motivation towards achievement. This study is a quasi experimental research with 2x3 factorial design. The study population was all students of class X of SMK Negeri 1 Geneng Odd Semester Academic Year 2019/2020 with a sample of class XTB2 and XDPIB2 students totaling 65 students. This sampling is random sampling. The instruments used to collect data are the initial mathematics ability test, student motivation questionnaire, and mathematics achievement test. Hypothesis testing uses two-way analysis of variance with unequal cells. The instruments used to collect data are test of prior knowledge in mathematics, achievement motivation questionnaire and mathematics achievement test. The testing of hypothesis uses two-way analysis of variance with unequal cell.The testing of hypothesis concludes that (1)Students who taught by learning model of NHT type have better achievement than students who taught by learning model of TGT type.(2) Students who have high achievement motivation have better achievement than students who have middle and low achievement motivation, also students who have middle achievement motivation have better achievement than students who have low achievement motivation.(3) There isn’t interaction between learning model andachievement motivation towards achievement.